HIV, other blood-borne viruses and sexually transmitted infections amongst expatriates and travellers to low- and middle-income countries: A systematic review - Crawford, Gemma; Lobo, R.; Brown, G.; Macri, C.; Smith, H.; Maycock, B. (Molecular Diversity Preservation International (MDPI), 2016)
In some high-income countries, a proportion of human immunodeficiency virus (HIV), other blood-borne virus (BBV) or sexually transmitted infection (STI) diagnoses have been reported as acquired overseas in low- and middle-income countries. A review was conducted to explore HIV, other BBV or STI related knowledge, risk behavior and acquisition amongst expatriates and travelers, particularly males, travelling from high to low- and middle-income countries. Seven academic databases were searched for 26 peer reviewed articles that met inclusion criteria. Significant variability in the studies was noted, in age, travel duration and frequency and outcomes/risk factors measured and reported on. Risk factors described included longer duration of stay; being single; travel for romance or sex; alcohol and other drug use; lack of travel advice; being male; higher number of sexual partners; and inconsistent condom use. Vaccination, pre-travel health advice, and having fewer sexual partners were described as protective. Studies are needed focusing on the social context in which risk-taking occurs. Better collaboration is essential to deliver comprehensive health promotion interventions alongside more consistent pre- and post- travel testing and advice. Policy measures are crucial, including consistent evaluation indicators to assess impacts of HIV, other BBVs or STIs in the context of mobility. Risks and responses for these epidemics are shared globally.